ChemInform Abstract: Phthalocyanine—Porphyrin Heteroarrays: A Perfect Marriage Between Two Unique Macrocycles. Issue 12 (14th March 2013) - Bottari, Giovanni; de la Torre, Gema; Guldi, Dirk M.; Torres, Tomas
Abstract Review: 131 refs.